DEVELOPMENT OF INFORMATION SYSTEM STUDENT PERIOD COMPLETION MOBILE-BASED - Alifya NFH; Ayu Tri Wardani; Edi Suhardi Rahman (Jurnal Media Elektrik, 2024)
This research aims to develop a mobile-based student study period completion information system in JPTE. The system developed uses the fountain development model approach with 5 stages, namely analysis, subsystem requirements, design, implementation, and testing. The purpose of choosing the fountain model is to ensure flexibility in development and adaptation to user needs. Black Box testing is carried out to ensure that each main feature, such as login, thesis/final project upload, journal upload notification, input and display of graduation dates, as well as management of student and KAPRODI data, functions according to the specifications set. The test results show that all 100% of the features successfully meet the expected functional criteria, with a system that is able to provide easy access, flexibility, and responsiveness. Overall, the Black Box test results show that the system is ready to be used by users and meets all the functional requirements that have been set. This mobile-based information system is expected to improve the efficiency of academic administration management and support the smooth process of completing the student study period.